Emma-Jean Lazrus fell in love - Tarshis, Lauren (New York, N.Y. Dial books, 2009)
The endearing, if not quirky, Emma-Jean Lazarus is back in the companion to Emma-Jean Lazarus Fell Out of a Tree. When Emma-Jean thinks about asking Will Keeler to the Spring Fling dance, she gets a fluttering feeling in her heart. What would someone like Will say to someone like Emma-Jean? After all, Emma-Jean is a little$1 (Bdifferent. Meanwhile, Emma-Jean's best friend, Colleen, has a secret admirer. With the Spring Fling just days away, she asks Emma-Jean to figure out who he is so maybe then Colleen could ask him to the dance. It's a perfect plan. But what Emma-Jean discovers could have consequences for everyone?.s
830L
93584